IMPROVING STUDENTS` SKILLS IN WRITING DESCRIPTIVE TEXTS BY USING ONLINE GROUP DISCUSSION: A STUDY AT SMPN 15 MALANG - Istichomah Isti Fania (Language-Edu, 2021)
Abstract: The present study was designed to explore how Online Group Discussion can improve the seventh-grade students` writing skill in descriptive text. To obtain the data, Classroom Action Research (CAR) in two cycles process starting from making lesson plan, implementation, observation, and reflection was employed. The quantitative data were obtained from the test and questionnaire and the qualitative data ware obtained from observation, students’ responses, and field-notes. After the implementation of the plan in cycle 2, the criteria of success were fulfilled. The mean score is 77.2 better than first test, 75.8. it means that the writing descriptive text of the students in the seventh-grade students at SMPN 15 Malang improve. Based on the findings, teachers are suggested to enact online group discussion in the class.Key words: Writing Skill, Descriptive Text, Online Group Discussion